The Effect of Learning Motivation on Learning Independence Among Eleventh Grade Students at SMA Labschool Universitas PGRI Semarang - Mufidah, Nur Aini; Yuliejantiningsih, Yovitha; Ismah, Ismah (The Future of Education Journal, 2024)
This study aims to determine the effect of learning motivation on learning independence among eleventh-grade students at SMA Laboratorium Universitas PGRI Semarang. Learning motivation is considered an important factor in achieving educational goals, while learning independence reflects students' ability to manage their own learning process. This research uses a quantitative approach with a correlational design, involving 87 students who were selected through a questionnaire. The collected data were analyzed using statistical techniques, including descriptive analysis and Pearson correlation. The results show that students' learning motivation and learning independence are in the "fairly good" category, with average scores of 91.06 and 85.09, respectively. Linear regression analysis shows a positive and significant effect of learning motivation on learning independence, with a significance value of 0.000 (p < 0.05). This means that the higher the students' learning motivation, the higher their learning independence will be. The study concludes that improving learning motivation can enhance students' learning independence. Therefore, it is recommended that teachers and schools pay more attention to factors that can increase students' learning motivation and provide facilities that support learning independence.